The treasure of biblical priamels from the Book of Proverbs – a semantic analysis - Lipińska, Magdalena; Szeflińska-Baran, Magdalena (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
Novitas is emphasized in biblical priamels from the Book of Proverbs both from the point of view of subject matter and their linguistic form. The validity of their subject matter stems from the fact that they belong to wisdom literature, which, according to the intentions of their authors, was supposed to the canon of conduct for the whole society. The researched proverbs depict the art of life being of potential interest to the recipient from the 21st century. Despite being marked by the realities from a different epoch, these sentences are still attractive content-wise. Next to individual references to the force majeure we find in priamels still valid comments on the human nature as well as timeless philosophy of life based on moderation, especially useful in the epoch of predominating consumerism. Explicit moral norms precisely define first and foremost types of behaviour and attitudes which we should avoid as well as those which are welcome.